The Factors Influencing Bullying Actions At School-Age Children In Elementary School 63 Lubuk Basung - Ningsih, Sri Wahyu; Sari, Dian (Jurnal Kesehatan - STIKes Prima Nusantara, 2018)
Bullying is one of the most aggressive acts in the world. Previous research in Indonesia found that 7 of 10 children were exposed by violence in schools. Factors causing bullying need to be identified to prevent high bullying in schools. This research aims to determine the factors that influence bullying action include individual factors, family factors, peer factors, school factors and media factors in school-aged children. The type of this research was descriptive analytic with cross-sectional study approach. The population in this study were children of school age grade IV, V and VI. The total sample in this research were 94 students and the sampling technique was purposive sampling. The data collection tool in this research was the questionnaire. The statistical test used was the Chi-Square test. The result ofÂ  bivariate data analysis shows that there is a significant correlation between individual factor (p= 0,0001), family factor (p = 0,0001), peer factor (p = 0,0001), school factor (p= 0,0001), media factor (p = 0,0001) with bullying in school-aged children. It is expected to the school to improve supervision and counseling to the students. Parents are expected to pay more attention to the activities doing by children and control the development of children.